Calculate 1 3 + 2 3 + 3 3 + . . . + 1 0 3 without a calculator (Hint: There's a formula for this).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice! I liked that you proved the formula.
1 3 + 2 3 + 3 3 + . . . + n 3 = ( 1 + 2 + 3 + . . . + n ) 2 = 2 n ( n + 1 ) 2 , so 1 3 + 2 3 + 3 3 + . . . + 1 0 3 = 2 1 0 × ( 1 0 + 1 ) 2 = 5 5 2 = 3 0 2 5
Problem Loading...
Note Loading...
Set Loading...
1 3 + 2 3 = 1 + 8 = 9 = 3 2
1 3 + 2 3 + 3 3 = 9 + 2 7 = 3 6 = 6 2
n = 1 , 2 , 3 are true
Assume n = k is true
When n = k + 1 ,
proved by Induction.
∴ 1 3 + 2 3 + . . . . + n 3 = ( 1 + 2 + . . . + n ) 2 = ( 2 1 0 ( 1 1 ) ) 2 = 5 5 2 = 3 0 2 5